2018
DOI: 10.1002/jmri.26015
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate utilization of cardiac magnetic resonance for the assessment of heart failure and potential associated cost savings

Abstract: 3 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…No study to our knowledge has previously determined cost savings associated with differing appropriate CCTA utilization in response to publication of the AUC. Our findings reporting potential cost savings associated with publication of the AUC are consistent with similar research performed on other imaging modalities, such as MRI [14,25].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…No study to our knowledge has previously determined cost savings associated with differing appropriate CCTA utilization in response to publication of the AUC. Our findings reporting potential cost savings associated with publication of the AUC are consistent with similar research performed on other imaging modalities, such as MRI [14,25].…”
Section: Discussionsupporting
confidence: 89%
“…The classification for each test was completed using retrospective patient data and occasionally by contacting the referring physician when needed. However, our classification methods were similar to those used in other studies with reported success rates for classifying patients > 95% [14,15]. The retrospective nature of the study also translated to a lack of granularity in some clinical parameters, such as the processes used by referring physicians to access the AUC guidelines.…”
Section: Limitationsmentioning
confidence: 90%
See 1 more Smart Citation